Function of Mass Communication in the Social Development of Afghanistan - Azizullah Sidiq (Integrated Journal for Research in Arts and Humanities, 2022)
Generally communication is one of the inseparable parts of every individual`s daily life. In terms of social development a prosperous society is mainly based on mass media which are defined as powerful tools for mass communication. Mass media contribute to various aspects of social developments in a society ranging from education, health, sports, agriculture, livelihood, freedom of speech, human rights, fight against corruption, and to public awareness. Mass media play a vital role in creating and shaping of public opinion and strengthening of the society. This study aims to review the key functions of mass media and its role in the social development of Afghanistan. Reviewed the literatures and Google Scholar was used to find out the recent studies. This study shows that Mass media itself emerged strongly and has played a vital role in the social development of Afghanistan especially public awareness, freedom of speech, sports, education, agriculture, and reconstruction.